Atrophy of Diaphragm and Pectoral Muscles in Critically Ill Patients - Vivier, Emmanuel; Roussey, Aurore; Doroszewski, Fanny; Rosselli, Sylvène; Pommier, Christian; Carteaux, Guillaume; Mekontso Dessap, Armand (Anesthesiology (Philadelphia), 2019)
Muscle atrophy is common in the critically ill, and diaphragm atrophy occurs during mechanical ventilation. It is not known whether wasting of diaphragm and nondiaphragm muscle is related. Ultrasound was used for serial assessment of diaphragm and pectoral muscle in 97 critically ill patients. Diaphragm and pectoral atrophy occurred in 48% and 29%, respectively, and was associated with septic shock (diaphragm) and steroid use (pectoral); atrophy of the two muscle types appears unrelated. Muscle atrophy occurs early during critical illnesses. Although diffuse, this atrophy may specifically affect the diaphragm under artificial inactivity accompanying invasive mechanical ventilation. The primary objective of this study was to highlight diaphragm atrophy during the first 5 days of critical illness. Monitoring of pectoral thickness (a nonpostural muscle with mainly phasic function) served as a control. Diaphragm and pectoral thicknesses were measured by ultrasound within the first 24 h of admission in 97 critically ill patients, including 62 on mechanical ventilation. Thirty-five patients were reexamined at day 5. Baseline median (interquartile) values of diaphragm and pectoral thicknesses at day 1 were 2.4 (2.0, 2.9) and 5.9 (4.7, 7.2) mm, respectively (n = 97). Higher values of diaphragm thickness at baseline were positively associated with male sex, chronic obstructive pulmonary disease, and diabetes. Diaphragm and pectoral atrophies (defined as a decrease of 10% or more between day 1 and day 5) were detected in 48% (17 of 35) and 29% (10 of 34) respectively, and were uncorrelated with each other. Diaphragm atrophy was significantly more frequent in patients with septic shock and in those with mechanical ventilation, as compared with their respective counterparts (71% [10 of 14] vs. 33% [7 of 21], P = 0.027 and 71% [17 of 28] vs. 0% [0 of 7], P = 0.004, respectively), whereas pectoral atrophy was more common in patients treated with steroids as compared with their counterparts (58% [7 of 12] vs. 14% [3 of 22], P = 0.006). A statistically significant association between diaphragm atrophy and outcome was not found. Pectoral atrophy seemed associated with less successful weaning from mechanical ventilation at day 14 (12% [1 of 8] vs. 58% [11 of 19], P = 0.043). Ultrasound enables identification of specific early diaphragm atrophy that affects the majority of mechanically ventilated patients and septic shock patients. Diaphragm atrophy and pectoral muscle atrophy seem to be two unrelated processes.